(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The Bardet-Biedl syndrome is a rare genetically heterogeneous, autosomal recessive inherited disorder with wide variability in expression. It presents with varied clinical manifestations like retinitis pigmentosa, polydactyly, central obesity, mental retardation and renal dysfunction. Other rare manifestations include diabetes mellitus, heart disease, hepatic fibrosis and neurological manifestations. Mutations in 16 genes have been identified as causative factors. We, here, have presented a 12 year old male patient exhibiting characteristic features of Bardet Biedl syndrome.